Estudo das propriedades mecânicas e termomecânicas de cerâmicas refratárias derivadas da cinza da casca de arroz e alumina calcinada - Quevedo, Juliana Calage (2020)
The Fronteira Oeste region of Rio Grande do Sul is the largest rice producer in Brazil. Culture plays a strategic role, both economically and socially. The Rice Husk appears as a by-product of great importance for the generation of electric energy, due to its high calorific value, and not less important, the ashes resulting from the burning process, rich in silica. The development of applications for Ash from the Rice Husk is strategic in order to enhance the generation of energy and close the cycle of rice cultivation with zero residues. This research aims to evaluate the physical, mechanical and thermomechanical properties of refractory ceramic materials produced with the incorporation of Ash from the Rice Husk and Calcined Alumina into its matrix. For the characterization of raw materials, Kaolin Clay, Rice Husk Ash, and Calcined Alumina, laser granulometry, fluorescence and x-ray diffraction tests were carried out. The manufacture of the samples (CPs) consisted of the partial replacement of Kaolin Clay by ash from the burning of the Rice Husk in the percentage of 10% in volume and by Calcinated Alumina, in the percentages of 10, 20 and 30% in volume. The ceramics were pressed at 42.5 MPa and sintered at a temperature of 1300 ºC. The physical properties of the CPs were investigated through the tests of linear retraction, mass variation, apparent porosity, water absorption, and apparent mass density. The mechanical properties were investigated through the tests of compressive strength and three-point bending resistance. The thermomechanical performance was evaluated by the thermal conductivity and thermal shock tests, while the fracture surface of the material was analyzed by scanning electron microscopy. The ceramics produced only with Clay Kaolin showed the best performance in the tensile strength in flexion in three points (28,1 MPa), a fact explained due to its lower porosity (9,6 %). When 10% of Rice Husk Ash was used, there was an increase in resistance to compression of 3,1%, but a reduction in resistance to flexion of 16,5 %, and an increase in the linear retraction of burning (5,4 %). The use of Calcined Alumina in the percentages of 30% resulted in an increase in the compressive strength (30,1%), flexural strength (11,6 %) and thermal shock resistance, in addition to a reduction in the linear retraction of burning (16,5%). The increase in resistance to thermal shock can be explained by the greater porosity (20,9 %), while the increase in resistance to compression and flexion is explained by the new phases formed such, in particular, Corundum (Al2O3-α). These new refractories can be used as thermal insulators in industrial furnaces.